2012
DOI: 10.1124/jpet.112.191783
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ritobegron (KUC-7483), a Novel Selective β3-Adrenoceptor Agonist, on Bladder Function in Cynomolgus Monkey

Abstract: We evaluated the pharmacological profile of ritobegron [KUC-7483; (Ϫ)-ethyl 2-[4-(2-{[(1S,2R)-2-hydroxy-2-(4-hydroxyphenyl)-1-methylethyl]amino}ethyl)-2,5-dimethylphenyloxy]acetate monohydrochloride] and its effects on the bladder in cynomolgus monkeys by in vitro and in vivo experiments. In vitro, ritobegron decreased the resting tension of the isolated bladder in a concentration-dependent manner (EC 50 8.2 Ϯ 2.3 ϫ 10 Ϫ7 M; maximal relaxation 88.7 Ϯ 3.7%). The ␤ 3 -adrenoceptor (AR) antagonist 3-(2-allylpheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…In enfluraneanesthetized cynomolgus monkeys intraduodenal administration of ritobegron dose-dependently reduced intravesicular pressure without significantly affecting heart rate or mean blood pressure, whereas i.v. administration of isoprenaline after ritobegron increased heart rate and reduced blood pressure (Maruyama et al 2012b).…”
Section: In Vivo Animal Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In enfluraneanesthetized cynomolgus monkeys intraduodenal administration of ritobegron dose-dependently reduced intravesicular pressure without significantly affecting heart rate or mean blood pressure, whereas i.v. administration of isoprenaline after ritobegron increased heart rate and reduced blood pressure (Maruyama et al 2012b).…”
Section: In Vivo Animal Studiesmentioning
confidence: 99%
“…KUC-7322 also depressed spontaneous contractions of rat colon with an EC 50 of 4.3 nM, and this was inhibited by SR 58,894A, indicating mediation via a β 3 -adrenoceptor (Yamazaki et al 2002). In the isolated cynomolgus monkey bladder, both KUC-7322 and isoprenaline were less potent than in the rat, but KUC-7322 remained a full agonist (Maruyama et al 2012b). Similar to the rat studies, KUC-7322 was considerably more potent for bladder relaxation than atrial beating rate or tracheal relaxation in the monkey, whereas, if anything, the opposite was true for isoprenaline (Maruyama et al 2012b).…”
Section: Isolated Tissue Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other β3 agonists have been reported in the literature: solabegron and ritobegron. Solabegron has been investigated in a phase II trial and has shown good results [Ohlstein et al 2012], whilst ritobegron has not yet been reported in human trials but has been shown to exhibit potent and selective β3 agonist activity in monkeys [Maruyama et al 2012].…”
Section: The Futurementioning
confidence: 99%
“…For instance, the agonist BRL 37,344 (Nahmias et al, 1991;Liggett, 1992), the weak partial agonist CGP 12,177 (((-)-4-(3-t-butylamino-2-hydroxypropoxy)- [5, H]benzimidazole-2-one) (Liggett, 1992), and the antagonist/ biased agonist L 748,337 (Candelore et al, 1999;van Wieringen et al, 2013) exhibit affinity differences of 10-fold or more between rat and human or rat and rhesus monkey b 3 -adrenoceptors, indicating important species differences in the ligand binding pocket; a better understanding of such difference awaits, resolving the crystal structure of b 3 -adrenoceptors. Based on such species differences, several investigators have turned to monkeys to explore properties of novel b 3 -adrenoceptor agonists (Maruyama et al, 2012;Hatanaka et al, 2013).…”
Section: Unique Ligand Recognition Profilementioning
confidence: 99%